Legal Issues in the Laws Governing the Enforcement of Foreign Arbitration Awards in Petroleum Disputes in Iraq - Mohammed, Haitham Abdulwahhab (2023)
Recognition and enforcement of international arbitration awards is the most important stage of arbitration, being one of the most important alternative methods for resolving petroleum disputes. When an arbitration award is issued, there are two ways to enforce it: The first is through voluntary (consensual) enforcement. The second is through judicial enforcement when the losing party refuses to respect the award. In order to enforce the arbitral award, the enforcement rules approved in each country shall be applied, taking into account the international conventions in this regard. Through doctrinal legal research methods, this research seeks to analyze the Iraqi laws that govern the enforcement of arbitration awards in petroleum disputes and to clarify the legal issues and challenges facing the enforcement of arbitration awards in Iraq, which are represented by the weaknesses of the Iraqi Code of Civil Procedures and the absence of a mechanism for enforcing arbitration awards in the Iraqi enforcement law and foreign court judgments, in addition to the existence of laws in force that prevent enforcement. The importance of this study lies in the necessity of developing the legal system for enforcing arbitration awards in Iraq to create a friendly environment for international arbitration, which will attract and encourage foreign petroleum investment in Iraq. Therefore, this study proposes a restructuring of the legal system for the enforcement of arbitral awards and the introduction of legislative improvements by enacting a new arbitration law, amending the Iraqi enforcement law, and repealing the law on the Protection of Funds, Interests, and Rights of Iraq from Inside and Outside Iraq.